Cover Feature: An Amino‐Functionalized Metal‐Organic Framework, Based on a Rare Ba12(COO)18(NO3)2 Cluster, for Efficient C3/C2/C1 Separation and Preferential Catalytic Performance (Chem. Eur. J. 9/2018). Issue 9 (19th December 2017) - Fan, Weidong; Wang, Yutong; Zhang, Qian; Kirchon, Angelo; Xiao, Zhenyu; Zhang, Liangliang; Dai, Fangna; Wang, Rongming; Sun, Daofeng
Abstract : An amino‐functionalized and Ba12 (COO)18 (NO3 )2 ‐based microporous metal−organic framework (UPC‐33) has been synthesized. UPC‐33 displays not only permanent porosity, but also high adsorption heat of CO2 and selectivity of CO2 /CH4. In addition, UPC‐33 exerts a high separation selectivity for C3 light hydrocarbons relative to CH4, and can selectively adsorb C3 H6 from C2 hydrocarbons. Based on the above work, the cover depicts a traditional Chinese‐style gossip image of UPC‐33, which acts as a platform for adsorbing C3 while separating C1 . More information can be found in the Full Paper by L. Zhang, D. Sun et al. onpage 2137 .